Non-Linearities in Fiscal Policy : The Role of Debt - Fotiou, Alexandra (IMF Working Papers; Working Paper, 2020)
Empirical evidence shows that fiscal multipliers depend on the state of the cycle, the nature of fiscal policy and the level of debt. In other words, evidence points to non-linearities in the effects of fiscal policy. This paper provides a framework to examine the role of the level of government debt in the assessment of consolidation policies across the business cycle, allowing for the consolidation multiplier to depend on the level of debt at the time of consolidation. The empirical analysis, which uses a panel of 13 countries between 1980 and 2014, finds that when debt is high, fiscal consolidations based on tax increases are in general self-defeating, in that they result in an increase of the debt-to-GDP ratio. Instead, cutting public expenditure has a less pronounced effect on economic activity and can stabilize debt. The initial level of debt in an economy, when a fiscal consolidation is implemented, appears to work as a channel in explaining evidence of state-dependence of the different consolidation instruments.